PENGARUH DISIPLIN TERHADAP KINERJA PEGAWAI DI DINAS PARIWISATA PROVINSI SUMATERA BARAT - Warman, Yudi; Silfeni, Silfeni; Ferdian, Feri (Journal of Home Economics and Tourism, 2017)
The research started from observation and experience of researcher whiledoing activity of industrial field experience at Tourism Office of West SumateraProvince, that there is descreasing performance to employee discipline in work.The purpose of research is to see how big the influence of variable discipline (X)to Employee Performance (Y) in the Tourism Office of West Sumatra Province.The sample of the in this research were 42 people taken using the technique ofsampling proportionate stratified random sampling. The data collection was donewith the questionnaire using scale likert that they are highly capable validity andreliability. This research result indicates that : (1) The discipline in the categorysufficient (45%), (2) The Employee Performance is at category sufficient (60%)(3) The discipline affect Employee Performance of 64,9 % and 35,1% influencedby other factors. Then obtained regression coefficient value of 0.880 with a valueof t arithmetic 8.608 on sig. 0,000 â‰¤ 0.05. This means that each increase of 1 unitdiscipline will increase 0.880 units of employee performance.